Extended high-gain observer-based output feedback control of underactuated quadrotor - Mohd Nor, Elya (2018)
Underactuated system is a nonlinear system having less actuators than the number of states to be controlled. The control for underactuated system is already a challenging task. It will be more difficult in the presence of external disturbances. Quadrotor is one example of an underactuated system. For quadrotor to overcome the external disturbance, it needs energy. However, energy limitation is the main challenges in quadrotor to serve the applications. An Extended High-gain Observer (EHGO) is proposed to stabilize the underactuated system in the presence of external disturbance with optimize energy consumption. In this study, the energy consumption is analyzed based on the control effort represented by control signal. EHGO has shown good potential to handle disturbances in the fully actuated system and underactuated system. In most studies, EHGO was successfully implemented on established board, which is of good quality but high cost. The capability of EHGO in the low-cost off-the-shelf common board has a high interest in a wide group of practitioners, hence it is worth investigating. Therefore, a control design framework and validation of EHGO - output feedback control (EHGO-OFB) for quadrotor trajectory tracking under broader flight envelope that is implementable in real-time using off-the-shelf common quadrotor platform is presented. A generalised closed-loop underactuated system model using EHGO-OFB in presence of disturbances was derived. An additional dynamic state equation is obtained which results in a closed-loop system in two-time-scale structure that is less complex. Consequently, this thesis extended the existing theorem of EHGO-OFB from fullyactuated to underactuated nonlinear system. The validation was performed in simulation and experimental. In simulation, the overall performance of EHGO-OFB in hierarchical controller (HC) improves the control effort by 36% from the standard HC. Meanwhile, the EHGO-OFB in sliding mode control (SMC) shows 15% improvement in the control accuracy achievable using smaller control effort compared to standard SMC. This simulation result provides an alternative to deal with chattering problem in SMC that has become the limitation of SMC when applied to a quadrotor. In experiment, a 39.64% improvement in the control effort was obtained for proposed EHGO-OFB based on existing hierarchical flight controller (HFC). The flight test was performed in the Indoor Space flight arena in Universiti Putra Malaysia using low-cost off-the-shelf common components with sampling rate of 0.01s. An EHGO gain of 0.01 was able to achieve a good performance for the quadrotor. The existing HFC based on PID algorithm rejects the disturbance by physical means and consume more energy whereas the EHGO-OFB reject the disturbance internally. The controller able to maintain the quadrotor in a bounded area with notably smaller control effort even in the presence of wind as external disturbance. The work in this thesis is expected to enhance the performance of quadrotor in various fields.